Answer:
p=-6
q=3
Step-by-step explanation:
5p-3q=-39
-2p-3q=3
Multiply the second equation by -1
2p +3q = -3
Add the first equation and the modified second equation
5p-3q=-39
2p +3q = -3
---------------------
7p = -42
Divide by 7
7p/7 = -42/7
p = -6
Now we can find q
2p +3q = -3
2(-6) +3q = -3
-12 +3q = -3
Add 12 to each side
-12+12 +3q = -3+12
3q = 9
Divide by 3
3q/3 = 9/3
q=3
It's 4 and u should know that by now.
<h3>
Answer: A) Dashed line, shaded below</h3>
=============================================================
Explanation:
2x + 4y < 16 solves to y < -0.5x+4 when you isolate y. The inequality sign does not change direction because we divided both sides by a positive value (in this case, 4).
The graph of y < -0.5x+4 will be the same as the graph of 2x+4y < 16
To graph y < -0.5x+4, we graph y = -0.5x+4 which is a straight line that goes through the two points (0,4) and (2, 3). This is the boundary line of the inequality shaded region. The boundary line is a dashed line because we are not including points on the boundary that are part of the solution set. We only include these boundary points if the inequality sign has "or equal to".
We then shade below the dashed boundary line to indicate points below the boundary line. The shading is done downward due to the "less than" sign.
---------------------
Perhaps another method to find what direction we shade is we can try out a point like (0,0). The point cannot be on the boundary line.
Plug those coordinates into either equation. I'll pick the second equation
y < -0.5x+4
0 < -0.5*0+4
0 < 0+4
0 < 4
The last inequality is true, so the first inequality is also true when (x,y) = (0,0). Therefore, the point (0,0) is in the shaded region. The point (0,0) is below the boundary line y = -0.5x+4
So this is another way to see that the shaded region is below the boundary line.
Answer:
Step-by-step explanation:
Unfortunately, your " 12×+9=10×1 " can be interpreted in more than one way. The symbol " × " should be used ONLY to indicate multiplication. Thus, " 12× " reads as ' 12x.' Then we have: 12x + 9 = 10. Unsure of what you meant by " 10×1". So I will treat your "10×1" as simply '10.'
Then we have 12x + 9 = 10, which reduces to 12x = 1 if we subtract 9 from both sides.
12x = 1 yields x = 1/12.
If this is not the result you expected, please go back to the original problem and share it as accurately as you can.
Answer:
oh so easy 4 my answer is so easy